Clinical pathological characteristics of the lupus nephritis - Leonardo Alberto Curbelo-Rodríguez (Archivo Médico de Camagüey, 2019)
Background: the lupus nephritis is a frequent and serious complication associated to the systemic lupus erythematosus. Objective: to characterize the lupus nephritis in the nephrology service of the University Hospital Manuel Ascunce Domenech. Methods: a descriptive, transverse and retrospective study was carried out in the Hospital Manuel Ascunce Domenech of Camagüey from January, 2012 to December, 2017. The universe was constituted for patients with systemic lupus erythematosus. As source clinical charts and forms made to empty data were used. The universe was constituted by all the patients with lupus nephritis whose biopsy was useful for the diagnosis. The variables were: age, sex, race, diagnosis criteria, histopathological stage, complications of the illness and noxious effects related with the treatment. Results: was found that four of each ten patients were between the 30 and the 44 years, while six of each ten were women. The fourth part of the sample was of the white race. The renal, cutaneous and hematologic approaches prevailed in the patients in that order. The histopathological patterns observed were the mesangial proliferation, the minimum changes and the membranous glomerulonephritis. The most frequent complications that were presented were the nephrotic syndrome and the chronic renal failure. The great majority of the studied patients presented as noxious effects of the treatment infections and cardiovascular manifestations. Conclusions: it is more frequent between 30 to 44 years, in women and in the white race. It is presented more as Nephrotic syndrome and chronic renal failure. The histopathological pattern more observed: the mesangial proliferation, minimum changes and membranous glomerulonephritis.